2009
DOI: 10.1074/jbc.m804812200
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-γ Targets Cancer Cells and Osteoclasts to Prevent Tumor-associated Bone Loss and Bone Metastases

Abstract: Interferon-␥ (IFN-␥ IFN-␥3 is a multifunctional cytokine produced mainly by NK cells and activated T cells that plays a critical role in host immune responses against pathogens and cancer (1). Mice deficient in IFN-␥, the R1 subunit of the IFN-␥ receptor, or the transcription factor STAT1 are more susceptible to spontaneous tumor development (1-3). IFN-␥ has also been found to have direct anti-proliferative and pro-apoptotic effects on tumor cells in animal models (4, 5); however, administration of high dose I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 43 publications
2
35
0
Order By: Relevance
“…It has been reported that IFN-γ has direct antiproliferative and proapoptotic effects on tumour cells in animal models (104,105) and that these effects prevent B16 experimental metastasis by directly inhibiting cell growth (106). We observed higher serum levels of IFN-γ and IL-17 in tumour-bearing hosts in Galectin-3 deficiency, which was not accompanied by differences in the number of CD4 + and CD8 + T cells in the spleen.…”
Section: Foxp3supporting
confidence: 51%
“…It has been reported that IFN-γ has direct antiproliferative and proapoptotic effects on tumour cells in animal models (104,105) and that these effects prevent B16 experimental metastasis by directly inhibiting cell growth (106). We observed higher serum levels of IFN-γ and IL-17 in tumour-bearing hosts in Galectin-3 deficiency, which was not accompanied by differences in the number of CD4 + and CD8 + T cells in the spleen.…”
Section: Foxp3supporting
confidence: 51%
“…IFN-g induced suppression of osteoclastogenesis is associated with down-regulation of cathepsin K (Kamolmatyakul et al, 2001). The antiresorptive properties of IFN-g may be of importance for prevention of tumorassociated bone loss and bone metastases (Xu et al, 2009).…”
Section: Interferonsmentioning
confidence: 99%
“…Despite its undoubted regulatory roles in osteoclast formation [10], IFN-g exhibited different functions in the in vitro and in vivo experiments. IFN-g was found to strongly inhibit osteoclast formation under in vitro condition, but IFN-g inhibited osteoclast formation directly [11] and promoted osteoclast formation indirectly [12] under in vivo condition.…”
mentioning
confidence: 96%